The Influence Of Perceived Credibility And Perceived Benefit On Customer Purchase Intention In Using BNI Mobile Banking - Maria G. Keintjem; David P. E. Saerang; Merinda H. Ch. Pandowo (PT. Inovasi Teknologi Komputer, 2024)
This study investigates the influence of Perceived Credibility and Perceived Benefit on customer Purchase Intention in using BNI Moobile Banking. Mobile banking has become increasingly popular in recent years, offering convenience and accessibility to financial services. This study examines the factors influencing customer purchase intention when using BNI Mobile Banking, with a specific focus on perceived credibility and perceived benefit. Through a survey of BNI Mobile Banking users, The context of the study was BNI mobile Banking user in Manado and a questionnaire was developed with 108 respondents. Three hypotheses were developed and tasted using multiple linear regression analysis. The results reveal there is No. significant influence between perceived credibility on purchase intention, there is a significant influence between perceived benefit on purchase intention and perceived credibility and perceived benefit is simultaneously influence purchase intention as the dependent variable.These findings offer valuable insights for financial institutions aiming to enhance customer engagement and encourage greater use of their mobile banking platforms.